A narrative review on the role of cognition, nutrition and energy availability in athletes of competitive sports to combat RED-S - Subalatha M.; Dhanush Rachaveti; Amutha S.; Ponpandi M. (PeerJ)
Background In the present scenario, competitive sports require athletes to achieve a phenomenal balance between cognitive abilities, motor skills, nutritional intake, and energy deficiencies. Such stability would enable the athletes to excel in their sporting field. Evidence shows that athletes develop specific cognitive abilities based on their sporting field. Nutrition is vital in creating an athlete’s cognitive ability and physical needs required to participate in competitive sports. The reduction in the intake of nutrients required before, after and during sports participation could result in relative energy deficiency in sports (RED-S), affecting the parts of the body. Methods The rationale behind the survey is to understand the role of nutrition and energy deficiency on the athletes’ cognitive abilities. The review’s research areas were identified as athletes’ cognition and nutrition in the context of RED-S. Search keywords were found based on the research area, such as “cognitive”, “nutrition”, and “energy deficiency/availability” in athletes. The search keywords were combined to form search queries (SQs). SQs were used to carry out the search on the Web of Science and Scopus databases. Results Sports play an important role in athletes’ cognitive abilities, such as decision-making, attention, memory, etc. Nutritional intakes, such as caffeinated, carbohydrate, alkaline, and protein-based supplements and diets, also significantly affect athletes’ cognitive and motor abilities. Low energy availability (LEA) causes cognitive and physical health problems in both female and male athletes. Conclusion The review identified that nutrition and LEA play crucial roles in athletes’ cognitive performance. Deficits in nutritional intake and energy availability lead to RED-S. Hence, cognitive performance could be used as an early indication to identify the nutritional and energy deficits in advance, enabling athletes to combat RED-S.